Weaning from invasive respiratory support in newborn: is there just one strategy? - Ventura, M. L.; Fedeli, T.; Ciarmoli, E.; Tagliabue, P. (Acta Biomedica Atenei Parmensis, 2014)
Despite a even more frequent use to non-invasive respiratory support, mechanical ventilation is still often necessary for supporting premature infants with lung disease. Protracted mechanical ventilation is associated with increased morbidity and mortality and thus the earliest weaning from invasive respiratory support is desirable. Weaning protocols may be helpful in achieving more rapid reduction in support. However, no consensus has been reached on criteria to identify when patients are ready to wean or how to achieve it. In this article, available evidence is reviewed and reasonable evidence-based recommendations for weaning and extubation are provided.